Safer peripheral settlements. Instruments in the design and evaluation of environmental quality - del Pozo Gómez, Fredy; Gómez, G. (Nexo Revista Científica, 2012)
The vulnerability of settlement before any situation and territorial scope, is a concern, due inter alia to their strong influence on the development policies of management to disaster or adverse external events affecting the normal development of the people; Summary to diagnose the environmental quality of urbanization in a discrete space, as it is the case of the peripheral housing estates, allows analyze those factors that influence the vulnerability of these and make recommendations for implementing environmental policies that mitigate the risks. On the basis of that vulnerability is a dynamic concept that examines the risk factors, continues an instrumental for environmental assessment of settlements population peripherals (APP), in particular the conditions of the city Santiago de Cuba, where it has considered this component in its evaluative indicators. You expose instrumentation reference and his categorical system: variable, subvariables, evaluative parameters and scale of values, which is the essence of the instrumental designed theorist; likewise are histograms and arrays that comprise the instrumental assessment workshop. It will serve to assess settlements in operation and for the design of new ones, and can be generalized to other territories. Key words: Peripheral population settlements, environmental quality, vulnerability DOI: http://dx.doi.org/10.5377/nexo.v24i2.659